2005
DOI: 10.1021/jo051936z
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Aqueous Chemistry of α-Acetoxy-N-nitrosomorpholine:  Reactive Intermediates and Products

Abstract: [reaction: see text] Alpha-acetoxy-N-nitrosomorpholine (7) has been synthesized starting by the anodic oxidation of N-acetylmorpholine in methanol. The 55% yield of N-nitrosomorpholinic acid, after cyanide-for-methoxy group exchange and hydrolysis, is an improvement of approximately 10-fold over our original 10-step method, and this is readily converted to 7. A study of the kinetics of decomposition of 7 in aqueous media at 25 degrees C and 1 M ionic strength was conducted over the pH range from 1 to 12. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Values of k obsd for the EA adduct attached to the exocyclic amino group of Gua, N 2 -EA-Gua, could not be measured due to irregularities in peak shape possibly due to the equilibrium between the hydrated aldehyde/aldehyde/alkene forms that could not be separated. Finally, for comparison, the rate constants were also measured for the EA adduct of benzimidazole, whose chemistry has been previously characterized, and these values are also included in Table .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Values of k obsd for the EA adduct attached to the exocyclic amino group of Gua, N 2 -EA-Gua, could not be measured due to irregularities in peak shape possibly due to the equilibrium between the hydrated aldehyde/aldehyde/alkene forms that could not be separated. Finally, for comparison, the rate constants were also measured for the EA adduct of benzimidazole, whose chemistry has been previously characterized, and these values are also included in Table .…”
Section: Resultsmentioning
confidence: 99%
“…While decomposition to the HE-nucleobase was detected by mass spectrometry to the extent of 1−3% during acid hydrolysis of the dimethylacetals, the kinetics of decay studied at neutral and basic pH indicated that the stability of the EA moiety attached to the purines is comparable to that when attached to benzimidazole. In an earlier study, it was noted that the EA-fragment attached to benzimidazole was quite stable at neutral pH, but its decay was accelerated in basic media and in the presence of primary and secondary amines . Thus, the possibility that the pendant amines of the purines might destabilize the EA fragment was anticipated.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…58 It decomposes cleanly, with first-order kinetics, via an N -nitrosoiminium ion intermediate (23), with the pH-rate profile showing acid-and basecatalysed regions, and an extensive pH-independent region between 3 and 9, the latter being ca 100 times slower than its C-analogue, the corresponding piperidine derivative. Implications for the interaction of N -nitrosomorpholine with DNA are discussed.…”
Section: Iminium Speciesmentioning
confidence: 99%